Long undecoded transcript isoform (LUTI) detection in meiotic budding yeast by direct RNA and transcript leader sequencing - Amy Tresenrider; Minghao Chia; Folkert J. van Werven; Elçin Ünal (STAR Protocols, 2022)
Summary: LUTIs (Long Undecoded Transcript Isoforms) are 5′-extended and poorly translated mRNAs that can downregulate transcription from promoters more proximal to a gene’s coding sequence (CDS). In this protocol, polyA RNA is extracted from budding yeast cells undergoing highly synchronized meiosis. Using a combination of long-read direct RNA sequencing and transcript leader sequencing (TL-seq), meiosis-specific LUTIs are systematically identified. Following identification, TL-seq is used to quantify the abundance of both LUTI and the more canonical gene-proximal (PROX) transcripts.For complete details on the use and execution of this protocol, please refer to Tresenrider et al. (2021).